Analysis of Senior High School Students’ Multi-Representation Skills on Newton’s Laws - Lole, Sri Wulandari; Supriyatman, Supriyatman; Syamsu, Syamsu; Untara, Ketut Alit Adi (Journal of Innovative Physics Education Research, 2025)
Physics learning is often considered difficult by students because it requires the ability to understand concepts verbally, mathematically, graphically, and diagrammatically. One of the subjects that demands these skills is Newton's Law. This study aims to analyze the level of students' multi-representation al skills in understanding Newton's Law in high schools in Palu City. This study uses a descriptive method with a quantitative and qualitative approach. Data were collected through a multi-representation skill essay test consisting of 5 questions and interviews. The research subjects were 12th grade students at four public high schools in Palu City (SMAN 1, SMAN 3, SMAN 4, and SMAN 7). The results showed that, in general, students' multi-representation skills were in the moderate category. A small number of students were in the high category, able to use various forms of representation consistently, while others were still in the low category, especially in graphical and mathematical representations. The conclusion of this study is that the multi-representation skills of high school students in Palu City regarding Newton's Laws are not yet uniform, with a tendency to be in the moderate category. This indicates the need for learning strategies that emphasize the use of multi-representation to strengthen the understanding of physics concepts.